The Shifting Value of Veil on Muslim Women and the Impact of Modernization - Rahmi; Ita Rodiah (al-Afkar, Journal For Islamic Studies, 2025)
Veil is a symbol of religious obedience for Muslim women. That is what continues to be believed until the occurrence of modernization which causes a value shift in the scope of the meaning of the veil. This article focuses on the scope of the veil which has become the lifestyle of Muslim women today. The approach used in this research is qualitative by conducting field studies in the form of observations around the Sleman area, Yogyakarta to observe Muslim women who use the veil with various models and types. In addition, this article also uses previous research as a foundation in research and to collect the data needed. After obtaining the data sought, data analysis is then carried out which is divided into three, namely data reduction, data presentation, and finally data verification on conclusion drawing. The result obtained is that modernization has a positive and negative impact on the veil users. The advantage is the progress in thinking of women who wear the veil so that they are not confined to the authority of men, while the disadvantage is the erosion of religious values from the use of veil which should have the main function to cover the intimate part (aurat) and curves of the female body and maintain women’s honor into a trend due to the influence of modernization. nevertheless, this article does not blame any hijab models used in daily life. Of course it goes back to the rights of each individual.